Experimental autoimmune encephalomyelitis causes skeletal muscle dysfunction in mice - Boesch, Julian; Ramseier, Pamela; Tisserand, Sarah; Pierrel, Eliane; Locatelli, Giuseppe; Summermatter, Serge (Frontiers in Neurology, 2025)
Multiple sclerosis (MS) is a neuroinflammatory disease affecting the brain and spinal cord and characterized by demyelination, neurodegeneration and chronic inflammation. More than 90% of people with MS present with peripheral muscle dysfunction and a progressive decline in mobility. Current treatments attenuate the inflammatory processes but do not prevent disease progression. Therefore, there remains an unmet medical need for new and/or additional therapeutic approaches that specifically improve muscle function in this patient population. The development of novel treatments targeting skeletal muscle dysfunction in MS will depend on suitable preclinical models that can mimic the human musculoskeletal manifestations of MS. Using a non-invasive approach to assess muscle function, we demonstrate in vivo that Experimental Autoimmune Encephalomyelitis (EAE) impairs skeletal muscle strength. Our data reveal a 28.3% (p < 0.0001) lower muscle force in animals with EAE compared to healthy control mice during electrically evoked tetanic muscle contractions that occur at intervals of 0.25 s and thus mimic fatiguing tasks. As we conduct force measurements by direct transcutaneous muscle stimulation in anesthetized animals, our setup allows for the repeated evaluation of muscle function, and in the absence of primary fatigue or reduced nerve input which constitute important confounding factors in MS. Taken together, our data highlight important similarities between MS in humans and EAE in mice with regards to skeletal muscle contractile impairments, and provide first evidence for a non-invasive in-vivo setup that will enable the preclinical profiling of novel drug candidates directed at specifically improving muscle function in MS.